(3GdTGed aj CUhd GdOjfs - (3YHO Gdedc Hf YHO Gddg Hf jhSa Hf eMeO GdLhjfj, CHh GdeYGdj, Qcf GdOjf, GdedbH HEeGe GdMQejf,J (B478 (3g` s
(3ChdgG (B:s
"(3aEf bjd ade jTJQW YOe GdYde ai UMI GdfXQ ? s
(3BNQgG (B:s
" (3aEf bGd bGFd (B: (3gPG jDOi Edi EKHGJ TjFjf cd hGMO efgeG TQW ai GdKGfi s
(3hgj eUhQI ai fSNI chHQjdis
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B160 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B184s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B130 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1024s
Keywords: (3GdJhMjO hGdedd hGdfMds